Dairy herd profitability: effects of milk yield and cost of production on net returns - F.D. Delano; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 1995)
Dairy cow herd enterprise records from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns to labor and management from 252 to 355 per cow. Returns for higher milkproducing cows were over 400 each. Cost per hundred weight of milk produced per cow for the higher-producing herds compared with lower-producing herds was about the same. In 1994, for every extra 1.00 spent on feed and other variable costs, the higher-producing herds earned 1.28.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995; Typo of author's name L. N. Langemeier; should be M. R. Langemeier.;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Profitability; Production costs; Production returns